Mr Attorney : the Attorney General for Ontario, in court, cabinet, and legislature, 1791-1899 - Romney, Paul, 1945- (Heritage., 1986)
In early Upper Canada the attorney general was little more than a skilled functionary -- the Crown's chief legal counsel; by the mid-19th century he had become a leading member of cabinet and generally premier. Mr Attorney is the story of this transformation and many other aspects of the attorney general's role in 19th-century Ontario.